2008
DOI: 10.1177/104063870802000628
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic Osteopathy Associated with Mycotic Pneumonia in Two Juvenile Elk (Cervus Elaphus)

Abstract: Abstract. Two yearling bull elk (Cervus elaphus) from the same farm developed anorexia, weight loss, and lameness. On physical examination, both elk were thin and showed diffuse swelling of all lower limbs. Radiographs of the lower limbs showed periosteal thickening of the distal extremities, consistent with hypertrophic osteopathy. Thoracic radiographs indicated the presence of pulmonary nodules. Cytologic evaluations of tracheal washes on both elk were consistent with inflammation. Acid-fast stains on both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…This reflex increases blood flow to the distal extremities and affects connective tissue and the periosteum. This theory was supported by the fact that there is a relief of symptoms following vagotomy or intercostal nerve resection (Lenehan and Fetter, 1985;Johnson et al, 1995;Ferguson et al, 2008).…”
Section: What Is Hypertrophic Osteopathy (Review Of the Literature)mentioning
confidence: 99%
See 3 more Smart Citations
“…This reflex increases blood flow to the distal extremities and affects connective tissue and the periosteum. This theory was supported by the fact that there is a relief of symptoms following vagotomy or intercostal nerve resection (Lenehan and Fetter, 1985;Johnson et al, 1995;Ferguson et al, 2008).…”
Section: What Is Hypertrophic Osteopathy (Review Of the Literature)mentioning
confidence: 99%
“…Among animals, hypertrophic osteopathy is observed in dogs most commonly (Brodey, 1971;Lenehan and Fetter, 1985;Johnson et al, 1995), but has also been reported in a variety of other domestic animals including the horse, cow, sheep, cat and in exotic species (Bush et al, 1974;Lenehan and Fetter, 1985;Godber et al, 1993;Curtis et al, 1997;van der Kolk et al, 1998;Morrison, 2002;Grierson et al, 2003;Ferguson et al, 2008). In animals, the term hypertrophic osteoarthropathy has not been used because the joints are not really involved (Montgomery, 2003;Piermattei et al, 2006); however, in human medicine, the term "osteoarthropathy" is still preferred because cases present with inflammatory arthritis (Armstrong et al, 2007;Dabir et al, 2007;Karkucak et al, 2007;Latos-Bielenska et al, 2007;Martinez-Ferrer et al, 2009;Nguyen and Hojjati, 2011).…”
Section: What Is Hypertrophic Osteopathy (Review Of the Literature)mentioning
confidence: 99%
See 2 more Smart Citations
“…HOA is found mainly in dogs (Headley et al, 2005;Cetinkaya et al, 2011;Lawler et al, 2015) and humans (Golder and Wolf, 2001;Utine et al, 2008), but has been observed occasionally in various other species (Lenehan and Fetter, 1985;Golder and Wolf, 2001;Mair and Tucker, 2004;Ferguson et al, 2008;Guyot et al, 2011). Although HOA was described in 1868 by Friedenreich (as cited in Kuhn et al, 2007), the exact aetiology remains unknown.…”
Section: Introductionmentioning
confidence: 99%